Kinetic Games and Their Impact on the Development of Some Adaptive Abilities and Behavioral Psychological Compatibility of Students with Slow Learning - Ammar Khaleel Ebrahim Al-Ezzi (Journal of Global Pharma Technology, 2016)
The interest in childhood and caring for the important trends in the present time because of the great impact in building their physical, dynamic and emotional as it is the basis on which to build the rest of his future life, the more well prepared by satisfying his needs in a suitable way to achieve psychological balance and social helped to build a personality from Where the strengths and weaknesses, and the researchers' observation of this class of students slow learning separated from their peers in one row and integrated only in the study of physical education and sports sciences and hence the importance of research by helping this group to become people The aim of the study was to identify the effect of motor games on the development of some adaptive abilities and the behavioral psychological compatibility of students of slow learning. The researchers hypothesized that kinetic games had an effect on the development of some compatibility abilities and behavioral psychological compatibility of learning slow learners. (10) Learning slow learners. After performing Pretests of some compatibility abilities and behavioral psychological compatibility, exercise exercises were performed for 9 weeks with two teaching units per week. The researchers found that there are significant differences for some compatibility abilities and behavioral psychological compatibility of the Pre and post-test and for the benefit of the post-test. The researchers attributed the reason for this to the effectiveness of motor games within the educational units as they were the age and abilities of the students, which helped satisfy their desires as a result of emptying their negative emotions and towards good performance The researchers recommend the need to use motor games, competitions and ball games that develop muscular compatibility as well as the establishment of courses for teachers of special education to develop the mental abilities of students slow.Keywords: Motor games, Harmonic abilities, Behavioral psychological compatibility and learning disabilities.